2008
DOI: 10.1007/s10815-008-9213-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated body mass index (BMI) does not adversely affect in vitro fertilization outcome in young women

Abstract: Obesity in young women does not adversely affect clinical pregnancy rates in patients treated with in vitro fertilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 40 publications
0
32
0
2
Order By: Relevance
“…A high prevalence of PCOS was seen in the obese category; therefore, the authors performed subset analyses comparing the BMI strata in the PCOS and non-PCOS groups. Whilst no significant differences were observed in the non-PCOS obese groups, it was observed that obesity in women with PCOS lead to a significant reduction in implantation and ongoing pregnancy rates (Martinuzzi et al 2008). Additionally, an interesting finding was that obese women were significantly more likely to encounter difficulty in observing the air bubble during ultrasound-guided embryo transfer and were more likely to have blood on or in the catheter after embryo transfer, factors which have been associated with poorer success rates after embryo transfer (Martinuzzi et al 2008).…”
Section: Obesity and Assisted Conceptionmentioning
confidence: 73%
See 2 more Smart Citations
“…A high prevalence of PCOS was seen in the obese category; therefore, the authors performed subset analyses comparing the BMI strata in the PCOS and non-PCOS groups. Whilst no significant differences were observed in the non-PCOS obese groups, it was observed that obesity in women with PCOS lead to a significant reduction in implantation and ongoing pregnancy rates (Martinuzzi et al 2008). Additionally, an interesting finding was that obese women were significantly more likely to encounter difficulty in observing the air bubble during ultrasound-guided embryo transfer and were more likely to have blood on or in the catheter after embryo transfer, factors which have been associated with poorer success rates after embryo transfer (Martinuzzi et al 2008).…”
Section: Obesity and Assisted Conceptionmentioning
confidence: 73%
“…In this study, obese patients had significantly lower ovulation rates at 6 months of treatment: 79% in women with BMI of 18-24 kg/m . Some authors, however, have been unable to demonstrate any difference in ovarian response to stimulation in obese women (Lashen et al 1999, Dechaud et al 2006, Martinuzzi et al 2008.…”
Section: Obesity and Assisted Conceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dokras et al [12] have emphasized that the obese women (with BMI > 40 kg/m 2 ) with PCOS had a lower ART cycle cancellation rate and fewer days of gonadotrophin stimulation than those without PCOS. Martinuzzi et al [23] have recently suggested that though total gonadotrophin dose was similar among all BMI groups, starting gonadotrophin dose was significantly lower in PCOS patients. In contrast, some authors have claimed that the presence of PCOS did not positively affect the duration of ovulation induction, cancellation rates and gonadotrophin dose [9].…”
Section: Ovulation Inductionmentioning
confidence: 91%
“…However, there are some studies showing no significant adverse effect of obesity on ovarian response during COH in ART cycles [14,21,23]. In addition, some other studies have revealed that obesity actually decreases the need for gonadotrophins [11,[20][21][22]24] and the number of days of ovarian stimulation [17,21,24] and does not affect the estradiol levels [9,[14][15][16][17][18]23,25].…”
Section: Ovulation Inductionmentioning
confidence: 99%